2015
DOI: 10.1016/j.cbi.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and species differences in the glucuronidation of glabridin with UDP-glucuronosyltransferases

Abstract: Glabridin (GA) has gained wide application in the cosmetics and food industry. This study was performed to investigate its metabolic inactivation and elimination by glucuronidation by use of liver and intestine microsomes from humans (HLM and HIM) and rats (RLM and RIM), and liver microsomes from cynomolgus monkeys and beagle dogs (CyLM and DLM). Both hydroxyl groups at the C2 and C4 positions of the B ring are conjugated to generate two mono-glucuronides (M1 and M2). HIM, RIM and RLM showed the most robust ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Unlike the cytochrome P450 enzymes, the UGT enzymes in mammals have significantly varying species differences in both expression and function, while the substrate and inhibitor spectra of the major UGT enzymes are much different from species to species (Higashi et al, 2014;Liang et al, 2011;Guo et al, 2015;Wen et al, 2007). In these cases, we predicted the potential risk of LCA-associated inhibition on human UGTs based on a series of available data (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the cytochrome P450 enzymes, the UGT enzymes in mammals have significantly varying species differences in both expression and function, while the substrate and inhibitor spectra of the major UGT enzymes are much different from species to species (Higashi et al, 2014;Liang et al, 2011;Guo et al, 2015;Wen et al, 2007). In these cases, we predicted the potential risk of LCA-associated inhibition on human UGTs based on a series of available data (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…GLA, a flavonoid extracts from the phytochemical licorice, has multiple biological activities [ 14 ], such as estrogen-like [ 26 ] and anti-inflammatory activities [ 27 ]. In addition, GLA can activate caspase-3, −8, and −9 to induce HL-60 cell apoptosis through the regulation of the p38 MAPK and JNK1/2 pathways [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Licorice root is a kind of traditional Chinese medicine that has been accepted for menopausal symptoms, coughing and fever [ 14 , 15 ]. Glabridin(GLA), an isoflavane compound in licorice roots, has attracted extensive attention because of its various biological properties, including the anti-proliferative [ 16 ], anti-stem cell-like [ 17 ], and anti-cancer activities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known to have whitening activity by suppressing the activity of tyrosinase during the synthesis of melanin and to help alleviate gastroenteric disorders. Recently, it was confirmed that glabridin is effective in metabolic syndromes, including hyperlipidemia, fatty liver, impaired glucose metabolism, diabetes, and obesity and has anti-inflammatory actions, anticancer actions, and the like [4]. However, in spite of useful medicinal efficacy, glabridin is easily broken down by sunlight, moisture, acidity, basicity, oxygen, heat, and the like due to low chemical stability, so it is very difficult to develop a product actually utilizing glabridin [4].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we synthesized a new pyranochromenylphenol derivative, HSG4112, by modifying the structure of glabridin. HSG4112 is stable under various physical conditions, while maintaining or improving its medicinal efficacy [4]. HSG4112 is a racemic compound with a chiral carbon.…”
Section: Introductionmentioning
confidence: 99%